STUDY OF THE INFLUENCE OF HEAT EXCHANGE EFFICIENCY IN A SHELL AND TUBE HEAT EXCHANGER ON HYDRODYNAMIC PARAMETERS - Rakhimov , Ganisher (Innovatsion texnologiyalar, 2023)
Currently, the world’s oil and natural gas are rich energy resources of minerals and the main source of energy and fuel production. Products obtained from their processing are widely used in all industries, transport and everyday life. Accordingly, by improving the design of heat exchangers used at natural gas processing enterprises, as well as by creating optimal hydrodynamic modes of movement of the raw material flow, it is possible to increase the overhaul period and increase economic efficiency.